Incorporating Requirements Management into DevOps - A Field Experiment at Combitech AB using T-Reqs - AlShriaf, Abdullatif; Wallin, Oscar (My University, 2024)
Context: Integrating Requirements Management (RM) into Agile and DevOps practices can address the lack of documentation and feature tracking in many agile projects. Objective: This study examines the implementation of RM within an agile workflow at Combitech AB, aiming to identify challenges, benefits, factors affecting developer acceptance, and propose effective adaptations. Method: Using action research, two intervention cycles were conducted with a software development team at Combitech, focusing on incremental RM adoption. Qualitative methods, including workshops and expert consultations, gathered data on its impact on the DevOps workflow. Conclusion: RM improves traceability and communication between developers and stakeholders but faces challenges like perceived intrusiveness and the need for upfront investment. Simplified RM practices and better requirement visualization enhance acceptance. Despite initial challenges, RM integration offers long-term benefits in communication and documentation, especially considering project complexity, team dynamics, and stakeholder engagement. The findings provide insights and strategies for successful Agile RM implementation.
Keywords: Agile; Requirements Management; DevOps; T-Reqs; Software Development; Action Research; Traceability